p120-catenin prevents multinucleation through control of MKLP1-dependent RhoA activity during cytokinesis - Robert A.H. van de Ven (Nature Portfolio, 2016)
The tumour suppressor p120-catenin (p120) controls cadherin-based adhesion. Here, the authors demonstrate that p120 regulates cytokinesis through binding to the centralspindlin component MKLP1 and controls RhoA activity. Loss of p120 in cancer induces multinucleation and chromosomal instability, independent of cell-cell adhesion.